(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Clinical studies involving of blood samples were randomly collected from out-patients in selected hospitals in the three (3) Senatorial districts of Kaduna State were examined for Plasmodium falciparum. Blood samples were collected from 1,918 patients attending the General Out Patient Department ward from various State Government owned hospitals in the three (3) Senatorial districts. Information obtained from questionnaires administered to out-patients who tested positive for P. falciparum revealed inconsistencies in the use of Insecticide Treated Nets (ITNs) and Chemoprophylaxis to prevent malaria. The most commonly used anti-malaria drugs for self-medication among patients from the three senatorial districts shows that 56.6% of the respondents in Kaduna North uses chloroquine/fansidar, 71.5% in Kaduna South and 67.0% in Kaduna Central. Many of the patients investigated do not have sufficient access and knowledge to ITNs as provided by the Roll Back Malaria programme or State malaria campaigns